229k views
0 votes
Verify that the function(s) solve the following differential equations (DES): a) y' = -5y; y = 3e-5x b) y' = cos(3x); y = į sin(3x) + 7 c) y' = 2y; y = ce2x , where c is any real number. d) y" + y' – 6y = 0 ; yı = (2x, y2 = (–3x e) y" + 16y = 0; yı = cos(4x), y2 = sin(4x)

User Imyousuf
by
5.4k points

1 Answer

2 votes

Answer:

In the step-by-step explanation, the verifications are made.

Explanation:

a)
y' = -5y

This one can be solved by the variable separation method


y' = -5y


(dy)/(dx) = -5y


(dy)/(y) = -5dx


\int (dy)/(y)  = \int {-5} \, dx


ln y = -5x + C


e^(ln y) = e^(-5x + C)


y = Ce^(-5x)

The value of C is the value of y when x = 0. If
y(0) = 3, then we have the following solution:


y = 3e^(-5x)

b)
y' = cos(3x)

This one can also be solved by the variable separation method


y' = cos(3x)


\int y' \,dy  = \int {cos(3x)} \, dx


y = (sin(3x))/(3) + K

K is also the value of y, when x = 0. So, if
y(0) = 7, we have the following solution.


y = (sin(3x))/(3) + 7

c)
y' = 2y

Another one that can be solved by the variable separation method


y' = 2y


(dy)/(dx) = 2y


(dy)/(y) = 2dx


\int (dy)/(y)  = \int {2} \, dx


ln y = 2x + C


e^(ln y) = e^(2x + C)


y = Ce^(2x)

C is any real number depending on the initial conditions.

d)
y'' + y' - 6y = 0

Here, the solution depends on the roots of the following equation:


r^(2) + r - 6 = 0


r = (-1 \pm 5)/(2)


r = -3 or
r = 2.

So the solution is


y(t) = c_(1)e^(-3t) + c2e^(2t)

The values of
c_(1), c_(2) depends on the initial conditions.

e)
y'' + 16y = 0

Again, we find the roots of the following equation:


r^(2) + 16 = 0


r^(2) = -16


r = \pm 4i

So we have the following solution


y(t) = c_(1)cos(4t) + c_(2)sin(4t)

The values of
c_(1), c_(2) depends on the initial conditions.

User Gtournie
by
5.6k points